Production and Characterization of Gelatin-Starch Polymer Matrix Reinforced with Cellulose Fibers. Issue 3 (August 2015) - Rodríguez-Castellanos, W.; Rodrigue, D.; Martínez-Bustos, F.; Jiménez-Arévalo, O.; Stevanovic, T.
In order to produce gelatin-starch polymer matrix reinforced with cellulose using twin-screw extrusion and compression molding, gelatin-potato starch and gelatin-corn starch formulations were plasticized with glycerol (25% w/w) and reinforced with cellulose (0.34% w/w and 0.68% w/w dry basis) to produce flat sheets. According to the analysis of variance performed, adding TEMPO-cellulose in the formulations decreased tensile strain at yield, but increased Young's modulus depending on the type of starch used in the formulation. Scanning electron microscopy and thermogravimetric analyses showed that the formation of a polymer matrix from gelatin/potato starch/TEMPO-cellulose and gelatin/corn starch/TEMPO-cellulose was successfully achieved.